Efektivitas media pembelajaran interaktif Wordwall dalam meningkatkan kemampuan membaca awal siswa - Iros Rosita; Ari Kartini; Asep Nurjamin; Agus Hamdani (Curricula: Journal of Curriculum Development, 2026)
Early reading skills are among the basic skills that elementary school students must master. Early reading difficulties persist among first-grade students, underscoring the need for effective instructional media to support learning. This study aims to assess the effectiveness of Wordwall interactive learning media in improving early reading skills among first-grade students at SDN Pasirwaru Limbangan. This study uses a quantitative approach with a one-group pretest-posttest pre-experimental design. The population in this study was all 21 first-grade students, who were also used as the research sample. Data were collected through reading comprehension tests before and after the implementation of Wordwall. Data analysis was performed using the Wilcoxon Signed-Rank Test, a nonparametric test, because one of the data sets was not normally distributed. The results showed a difference in reading comprehension between before and after the use of Wordwall. These findings indicate that Wordwall interactive learning media is effective in teaching reading comprehension to first-grade elementary school students.